Micro versus Macro Shear Bond Strength Testing of Dentin-Composite Interface Using Chisel and Wireloop Loading Techniques - Ahmed M. Ismail; Christoph Bourauel; Ahmed ElBanna; Tarek Salah Eldin (Dentistry Journal, 2021)
Shear bond strength (SBS) testing is a commonly used method for evaluating different dental adhesive systems. Failure mode analysis provides valuable information for better interpretation of bond strength results. The aim of this study was to evaluate the influence of specimen dimension and loading technique on shear bond strength and failure mode results. Eighty macro and micro flowable composite cylindrical specimens of 1.8 and 0.8 mm diameter, respectively, and 1.5 mm length were bonded to dentinal substrate. Four study groups were created (n = 20): Macroshear wireloop, Gp1; Microshear wireloop, Gp2; Macroshear chisel, Gp3; and Microshear chisel, Gp4. They were tested for SBS using chisel and wireloop loading devices followed by failure mode analysis using digital microscopy and SEM. Two- and one-way ANOVA were used to compare stress at failure values of different groups while the Kruskal–Wallis test was used to compare between failure modes of the tested groups. Gp4 recorded the highest mean stress at failure 54.1 ± 14.1 MPa, and the highest percentage of adhesive failure in relation to the other groups. Specimen dimension and loading technique are important parameters influencing the results of shear bond strength. Micro-sized specimens and chisel loading are recommended for shear testing.